British men’s magazines’ scent advertising and the multimodal discursive construction of masculinity: a preliminary study - Gregorio-Godeo, Eduardo De (Estudios Ingleses de la Universidad Complutense, 2009)
This paper presents a preliminary study of the multimodal discourse on masculinity constituted in contemporary British men’s magazines’ perfume advertising pages. In particular, this contribution intends to delineate what might be taken to be appropriate research directions for further empirical investigations on the discursive construction of masculinity in a genre of multimodal nature where images feature more prominently than language. Through a methodological integration of Kress and van Leeuwen’s (1996) social semiotics framework and Fairclough’s (1995b) CDA methodology for the examination of media discourse, the present study aims to shape the hypothesis that the discursive construction of masculinity carried out in these perfume advertisements – embedded into the sociocultural matrix accounting for its emergence – is multimodally articulated, thereby attempting to fix some analytical categories for any further empirical investigations necessary for providing specific results about the discursive construction of the masculine in this genre. In so doing, this piece does not claim any ‘results’ as such – which would have certainly demanded an examination of a wider corpus – but makes explicit certain hypotheses for further corpus-based research.